Pengaruh Kepercayaan Konsumen Terhadap Developer Dalam Pelaksanaan Perjanjian Pengadaan Perumahan - Raditya Ibnu Rizach; Latif Assidik; Muhammad Alif Ramadhan; Muhammad Arib Yahya (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2023)
The main problem examined in this context is how the developer fulfills its obligations to consumers who have made payments. The method used is banking mediation, aiming to provide a comprehensive, complete, and systematic overview of the implementation. This research is descriptive, where conclusions are drawn from general issues faced by consumers regarding specific problems. Furthermore, legal materials are analyzed to see if they can provide a solution or an overall picture of the issue. Thus, this study attempts to provide a comprehensive understanding of conflict resolution between developers and consumers in the context of housing development in Indonesia